Effect of microwave processing on the physical, physicochemical and rheological properties of wheat grain and its flour (Research, Society and Development, 2021)
A pilot system for the application of microwaves to foods, with a frequency of 2.45 GHz, and microwave powers ranging from 100 W to 3000 W was used to evaluate the effects of this technology on physical, physicochemical and rheological characteristics of wheat grains, wheat flour and their respective gluten. Wheat samples (600 g per treatment) were conditioned to moisture of 23% and exposed to microwaves in the powers of 100 W, 450 W and 750 W (TM 1, TM 2 and TM 3, respectively) until it reached 16 % and had their characteristics compared with control wheat (TC), without treatment. The results of milling yield and specific volume of grains did not show significant differences (p≤0.05). These wheats were ground, generating flours FM 1, FM 2, FM 3 and FC (from TM1, TM 2, TM 3 and TC, respectively). The results of wheat flour damaged starch from wheat-treated and FC showed no significant difference between their averages. Flours FM1, FM 2 and FM 3 showed significant reductions in the values of wet and dry gluten, when compared to the FC, but their gluten indexes were not statistically different. With the exception of the paste temperature, other pasting properties (maximum viscosity, minimum viscosity, breakdown and final viscosity) were significantly different, at the level of 5% significance, and presented a progressive behavior of the viscosity profile. The size distribution of the particle, accumulated at 90%, for flours FM 1, FM 2 and FM 3 were larger than the accumulated flour of FC and different significantly, confirmed by the higher values of their mean diameters (d4,3). The polydispersity of the particles (Span), ranged from 1.81 to 1.94, and there was no significant difference between all samples, however due to the value obtained being greater than 1, this indicates that the samples are polydispersed.